Impactos da urbanização no coeficiente de escoamento : estudo de caso em bairros do município de Passo Fundo - Silva, Júlia Lorenzato (2022)
Urbanization in Brazil was intensified with industrialization. Linked to urbanization is the increase in soil sealing, suppression of vegetation, increased risk of flooding and, therefore, loss of environmental quality in the area. The surface runoff and the runoff coefficient are directly linked to the consequences of urbanization, since as the permeable areas decrease, the surface water flow increases. The purpose of the study was to analyze the behavior, currently and in future projections, of the runoff coefficient and surface runoff with the urbanization process in the Boqueirão and Centro neighborhoods, both in the city of Passo Fundo. The analyzes were made from 3 runoff coefficients chosen from the literature, namely the roof, unimproved surface and vegetation for the creation of land use and occupation maps. With the use of a weighted average to calculate the runoff coefficient and the calculation, based on the rational method, for surface runoff, it was possible to analyze that, both in the Boqueirão neighborhood and in the Centro neighborhood, over the 11 years between the maps performed, obtained a growth in vegetation and roof surface, but the growth of the green area became insignificant, as the roof areas became larger over the years. With the calculated coefficients and the projections carried out for 33 years, it was concluded that the outflow of the Boqueirão and Centro neighborhoods had a constant increase, mainly due to the negative points of the increase in the superficial coefficient, such as, for example, soil impermeability.